Analisis Kelayakan dan Strategi Pengembangam Usaha Ternak Sapi Potong di Daerah Perbaungan Sumatera Utara - Suci Dian Cahya; Lia Maudya; Ilda Syahfitri; Fauziah Fauziah; Kiagus Muhammad Zain Basriwijaya (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
This study aims to analyze the feasibility of beef cattle farming in the Perbaungan area, North Sumatra, and to develop sustainable business development strategies. The approaches used include financial, technical, and market analysis, with data collected through field surveys, interviews with farmers, and secondary data analysis. The results of the study indicate that the beef cattle farming business in this location is economically feasible with a significant level of profit. Recommended development strategies include optimizing feed management, increasing human resource capacity, and product diversification to expand the market. These findings are expected to help local farmers improve their business productivity and contribute to national food security.